Profile-based video design for motion graphics: a case study of the multimedia engineering technology study program at Boash Indonesia Digital Polytechnic - Rahayu, Meita Sekar; Pohan, Amir Hamzah; Khadijah, Khadijah; Sanwasih, Mochamad; NA, Charmiyanti (Privietlab, 2024)
A company profile is a detailed representation of a company, aimed at attracting customer attention and interest. Among the various forms of company profiles, video is one of the most effective. The Multimedia Engineering Technology Study Program at Boash Indonesia Digital Polytechnic (PDBI) currently lacks a profile video, which could serve as a significant promotional tool. This research aims to develop an informative and promotional medium in the form of a motion graphic-based profile video. The method employed is the Multimedia Development Life Cycle (MDLC). The resulting motion graphic-based profile video is designed to support promotional activities, presented in an educational and communicative manner to ensure effective delivery to the audience.